Antioxidant effects of methanolic extracts of Anthemis Susiana Nabelek, Alyssum campestre, and Gundelia tournefortii - Farhanaz Changaee; Mohammad Ali Goudarzi; Runak Ghobadi; Pouya Parsaei (Caspian Journal of Environmental Sciences)
One of the prominent effects of free radical activity in the body is damage to biological and vital molecules such as nucleic acids, proteins and lipoprotes. So, free radicals, especially reactive oxygen species, play an important role in medical issues. Using compounds that neutralize free radicals, i.e. antioxidants, is a suitable choice to minimize the damage caused by their production. Herbs are recognized as rich sources of antioxidants and consumption of these plants can be effective for human health. The present study was conducted to evaluate the antioxidant property of native medicinal plants including Babouneh shoshi, Anthemis Susiana Nabelek, Ghodoumeh dokhtari, Alyssum campestre, and Kangar, Gundelia tournefortii in Ilam Province, Iran. Total antioxidant capacity was measured using at 570 nm with the enzyme-linked immunosorbent assay (ELISA). The results showed that the total antioxidant capacities of Babouneh shoshi, Ghodoumeh dokhtari, and Kangar are 4.29, 1.01 and 1.25 mmol Fe2+ L-1, respectively. Generally, there are several natural antioxidant compounds in Iranian medicinal herbs which made them as reliable sources for therapeutic purposes. The essential oils of these plants are the source of herbal secondary metabolites with antioxidant and antimicrobial effects that are recommended for their use in the food, pharmaceutical, and health industries.